Strategic planning for smart cities: a case study of Maribor's transformation based on existing strategies - Vito Bobek; Boštjan Štuhec; Lea-Marija Colarič-Jakše; Tatjana Horvat (Mednarodno Inovativno Poslovanje)
Background: Maribor faces challenges in transitioning to a smart city, requiring strategic planning that integrates technology and sustainability. Objectives: To develop a comprehensive strategic framework for Maribor's smart city transformation. Methods/Approach: Qualitative methods, including interviews with stakeholders, document analysis, and comparative case studies with other cities, were used to assess Maribor’s strategic needs. Results: Key findings emphasize the need for infrastructural upgrades, public-private partnerships, and community engagement, offering actionable recommendations for sustainable urban development.